Energy efficiency of small cell backhaul networks based on Gauss–Markov mobile models. Issue 2 (1st March 2015) - Ge, Xiaohu; Tu, Song; Han, Tao; Li, Qiang; Mao, Guoqiang
Abstract : To satisfy the recent growth of mobile data usage, small cells are recommended to deploy into conventional cellular networks. However, the massive backhaul traffic is a troublesome problem for small cell networks, especial in wireless backhaul transmission links. In this study, backhaul traffic models are first presented considering the Gauss–Markov mobile models of mobile stations in small cell networks. Furthermore, an energy efficiency model of small cell backhaul networks with Gauss–Markov mobile models has been proposed. Numerical results indicate that the energy efficiency of small cell backhaul networks can be optimised by trade‐off the number and radius of small cells in cellular networks.